Upaya Meningkatkan Kemampuan Kognitif Mengenal Bilangan 1-10 melalui Permainan Congklak pada Siswa Kelompok A TK Idhata 2 Pule, Trenggalek - Sulasmi, Sulasmi (Universitas Nusantara PGRI Kediri, 2023)
Counting or counting is one of the areas of development in cognitive abilities that is developed at Idhata 2 Pule Kindergarten, Pule District, Trenggalek Regency. However, from the results of research carried out in learning numeracy at Idhata 2 Pule Kindergarten, learning numeracy has not achieved the expected learning objectives. This can be seen from the results of observations of 16 children, only 4 children had good numeracy skills according to their stage of development. From the results of observations made in counting 1-10 activities at Idhata 2 Pule Kindergarten, some children are not able to count 1-10 well, this is because counting or counting activities are mostly done using conversation and without using media that attracts children's interest. . Based on the description above, the researcher conducted classroom action research which was carried out from September to October 2020. Meanwhile, the class used as the research object was group A students, totaling 15 children. The results of the research on increasing cognitive abilities regarding the material of recognizing numbers 1-10 through the congklak game were that in Cycle I the percentage of classical completeness was 50% while in Cycle II it was 81%, an increase of 31%.